Breaking the mold : women, men, and time in the new corporate world - Bailyn, Lotte (Free P. New YorkUS, 1993)
Uses real life cases to illustrate common problems which employees encounter as they seek to co-ordinate work and private life. Argues that companies need to give the private needs and concerns of their employees a legitimate place in the planning of work. Examines the traditional corporate mold and its negative effects on organizations and employees; and analyzes the response of organizations to the emerging difficulties and conflicts. Identifies and examines the key issues that need to be rethought, and on which solutions will depend. Lists these issues as: the meaning of time, of commitment and of career success.